2005
DOI: 10.1166/jnn.2005.508
|View full text |Cite
|
Sign up to set email alerts
|

RNA Helicases: Versatile ATP-Driven Nanomotors

Abstract: RNA helicases are a large family of molecular motors that utilize nucleoside triphosphates to unwind RNA duplexes and to remodel RNA protein complexes. In this review, we discuss the structure and function of RNA helicases with an emphasis on the potential application of these enzymes to control conformational changes in nanoassemblies that contain RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…µ was used to denote the expectation of yields when there was no mutant, hence µ A ( X i , Z,K ) could be considered the theoretical yield of phi29 virion at the condition X i . log 10 ( Y i )~ N (log 10 (µ A ( X i , Z,K )), 2 was assumed. Thus, measurement errors for Y i increased exponentially as the percentage of functional motors, A ( X i , Z,K ), increased.…”
Section: Resultsmentioning
confidence: 99%
“…µ was used to denote the expectation of yields when there was no mutant, hence µ A ( X i , Z,K ) could be considered the theoretical yield of phi29 virion at the condition X i . log 10 ( Y i )~ N (log 10 (µ A ( X i , Z,K )), 2 was assumed. Thus, measurement errors for Y i increased exponentially as the percentage of functional motors, A ( X i , Z,K ), increased.…”
Section: Resultsmentioning
confidence: 99%
“…These include RNA helicases, actin‐myosin, dyneins and kinesins, among others (Hess et al. 2004; Jankowsky et al. 2005).…”
Section: Applications In Nanobiotechnologymentioning
confidence: 99%
“…Obvious candidates for factors involved in remodeling RNPs during localization are RNA helicases. Many aspects of RNA metabolism involve helicases, which can act in an ATP-dependent manner to either unwind duplex RNA or alter protein-RNA interactions (reviewed in Jankowsky et al, 2005). Recently, Fairman et al (2004) demonstrated that RNA helicases can remove proteins from an RNA duplex without unwinding of the RNA suggesting that the ''RNPases'' can remodel a variety of RNP interactions.…”
Section: Remodeling By Rearrangement: Helicases At Work?mentioning
confidence: 99%